Notions of sustainable urban planning and impacts on Habitation - Ghasan Hasan Mahmood (Wasit Journal of Engineering Sciences)
One of the main housing problems in the modern era emerged from the case of environmental and urban degradation and the accompanying population growth and an increasing scarcity of natural resources, which has established itself firmly on the planning status of contemporary in an attempt to find appropriate solutions to this problem orientation was towards the concept of sustainability, which in turn is a global demand necessary contributes mainly in the treatment of a lot of this problem and then configure the general perception of the concept and methodology to be applied to urban and urban areas, which are aimed at forming healthy urban environment, health, social, urban and environmentally suitable for all economic groups in society, and I have touched on the concept of sustainability and its history briefly , as well as sustainable development and the basics of sustainable urban planning with the definition of the structure of the city's urban and address standards of planning, and has been eating Neighbourhood Unit  being the main Aalouhdh in the structure of the urban city. with the development of the most important sustainable planning in detail the concepts with Astertajat application of these concepts in the neighboring implications the residential environment as a model can be a start for the dissemination of sustainable planning applications in urban design and urban planning of our cities contemporary line To be the problem of the research is that the residential neighborhoods in contemporary cities suffer from the weakness evident in the achievement of the principles of urban sustainability in the built environment as a result of the lack of a clear vision of the great impact of the application of sustainable urban planning concepts on housing environment residential neighbors and especially those that are considered fundamental group unit for the emergence of cities and the wealth of the solution to the problems of the expansion of agricultural land and not to the depletion of natural resources, agricultural land and reduce the energy consumption and therefore reduce the various infections with developing the economy and raising the social level of the communities Alexanah.lzlk the aim of the research is centered on asking perceptions affecting the concepts of sustainable planning and environmental, social, economic, physical and its effects on residential environment with taking as a model .oantaleg neighboring residential search in the premise that the implementation of sustainable urban planning concepts will create residential Abih sound and healthy, safe and socially homogeneous and compact urban .